2019
DOI: 10.1177/0891988719862622
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Status of Elderly Patients With Severe Mental Disorders in Rural China

Abstract: This study was performed to compare the treatment status between older (≥65 years) and younger adults (18-64 years) with severe mental illness (SMI) and explore factors associated with treatment status in rural China. Persons with SMI were identified in one mental health survey in 2015 in 6 townships of Xinjin County, Chengdu, China. Logistic regressions were conducted to explore factors associated with treatment status. Older adults with SMI, especially major depressive disorder, reported significantly lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…As the world population continues to age, there are more people living with depression, and many of them are underdetected 14 and untreated. 19 Our study has provided evidence of the impact of older age depression subcases on increased risk of all-cause mortality. Moreover, older people with subcases of depression face a comparable risk of all-cause mortality to those with full cases of depression.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…As the world population continues to age, there are more people living with depression, and many of them are underdetected 14 and untreated. 19 Our study has provided evidence of the impact of older age depression subcases on increased risk of all-cause mortality. Moreover, older people with subcases of depression face a comparable risk of all-cause mortality to those with full cases of depression.…”
Section: Discussionmentioning
confidence: 69%
“…The stronger impact of depression on all-cause mortality in the older Chinese population could be due to high levels of socioeconomic deprivation, depression under-detection for treatment and low levels of health care and medications. 7,14,19 The findings of our study from China-the largest LMIC, which accounted for important co-variables including low educational level, rural areas and financial difficulties, could suggest an independent impact of depression on excess mortality regardless of country or region, although the magnitude of the impact varied in older people with depression subcase and case among different populations. Studies in the HICs and West 3,20,21 showed that older men with depression case versus non depression had a higher RR of all-cause mortality than their female counterparts.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…To date, little is known about treatment status and patterns in older people with severe mental illness in China. Chen et al 21 examined the treatment status of older patients with schizophrenia, bipolar disorder, or major depressive disorder in rural areas of China and explored their associated factors. They used the Andersen's behavioral model, a theoretical framework for health services use in older population, which includes individual determinants of health service use: predisposing, enabling, and need.…”
Section: Recent Clinical Research In Geriatric Psychiatry and Relatedmentioning
confidence: 99%
“…In addition, the accompanied high side effects of antidepressants can cause non-adherence, which was found to influence about 30% of depressed patients within 1 month and up to 60% within 3 months [ 9 ]. This is a major challenge and may worsen depressive symptoms or lead to other age-related diseases in older adults [ 10 ]. Therefore, optimizing clinically meaningful, non-pharmacological adjunctive therapies for depressed older adults will be important, considering the rapid population ageing and the consequent increasing healthcare demands [ 4 ].…”
Section: Introductionmentioning
confidence: 99%